Peran Supervisi Pendidikan dalam Meningkatkan Mutu Pendidikan - Suparliadi Suparliadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to determine the role of educational supervision in improving the quality of education. This research is qualitative with case study method. The data obtained were compiled, analyzed, and concluded so as to obtain conclusions regarding the study of literature. The results of the study showed that educational supervision has the following functions, a) as a coordinator he can coordinate teaching and learning programs, the duties of staff members for various activities that differ among teachers; b) as a consultant he can provide assistance, together with consulting problems experienced by teachers both individually and in groups. In accordance with the use of the supervision technique; c) as a group leader he can lead a staff of teachers in developing the potential of the group, while developing the curriculum, subject matter and professional needs of teachers together; d) as an evaluator he can help teachers in assessing the results and learning process, can assess the curriculum that is being developed. Judging from the definition and function, supervision plays a very important role in improving the quality of education. In conclusion, educational supervision plays a role in providing convenience and helping principals and teachers develop their potential optimally. Keywords: Education Quality, Education Supervision